2016
DOI: 10.1007/s12031-016-0780-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Scopolamine Treatment on Cognitive Impairments and Myelin Basic Protein Expression in the Mouse Hippocampus

Abstract: Myelin plays an important role in learning and memory, and degradation of myelin is a key feature in the pathogenesis of neurological disorders involving cognitive dysfunction. Myelin basic protein (MBP) is one of the most abundant structural proteins in myelin and is essential for myelin formation and compaction. In this study, we first examined changes in the distribution of MBP-immunoreactive myelinated fibers and MBP levels according to hippocampal subregion in mice following chronic systemic treatment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 40 publications
(38 reference statements)
4
17
0
Order By: Relevance
“…In our preliminary study, we found that there were no significant differences in protein levels of NFs in the hippocampus between 3 and 4 weeks SCO-treated groups. For reference, we recently reported that significant difference in the protein level of myelin basic protein, which is most abundant structural protein in the myelin, was not found in the hippocampus between 3 and 4 weeks SCO-treated groups ( 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our preliminary study, we found that there were no significant differences in protein levels of NFs in the hippocampus between 3 and 4 weeks SCO-treated groups. For reference, we recently reported that significant difference in the protein level of myelin basic protein, which is most abundant structural protein in the myelin, was not found in the hippocampus between 3 and 4 weeks SCO-treated groups ( 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The animals used in the passive avoidance test were used for spatial learning and memory test using the Morris water maze task according to our published protocol ( 4 ). In short, a circular pool (90 cm in diameter and 45 cm height) filled with water was conceptually divided into four quadrants, and a platform (6 cm in diameter and 29 cm in height) was placed in one quadrant 1 cm below the water surface.…”
Section: Methodsmentioning
confidence: 99%
“…SCO was administered by intraperitoneal injection once daily for 4 weeks, and vanillin or 4-HBA were administered orally using a feeding needle once daily for 4 weeks. Experimental dosage of SCO, vanillin, and 4-HBA was selected on the basis of previous studies [2022]. …”
Section: Methodsmentioning
confidence: 99%
“…Spatial learning and memory test was performed using the Morris water maze test according to a published procedure by Park et al [22]. In short, a circular pool (90 cm in diameter and 45 cm height) filled with water was conceptually divided into four quadrants, and a platform (6 cm in diameter and 29 cm in height) was placed in one quadrant 1 cm below the water surface.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation